Las colonias escolares durante la Guerra Civil : el caso de la colonia de Navajas de la Diputación de Madrid como contrapunto a la propaganda - Karine Lapeyre (Cahiers de Civilisation Espagnole Contemporaine)
As the Spanish Civil War unfolded, battles were military and ideological. In what could be considered a propaganda battle, children became the center of all attention. When the Junta de Madrid decided to evacuate the capital city, it sent children to the colonies. The press narrated their evacuation and their relocation to Levante. It all seems ideal. The new model of society which was championed by republican forces was born. It was founded on a fair society for all where children would take center stage. However, the reality was very different. With war and its consequences, it became impossible to achieve the original objectives. The press was forbidden to express it. Archives and testimonies from after the Francoism are the only places where one can find traces of the flaws in this children relocation system. After the war, the opposition to the republican forces would also use the relocation system but with a different approach.